2020
DOI: 10.1089/heq.2020.0030
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on African American Communities in the United States

Abstract: Purpose: The purpose of this ecological study was to understand the impact of the density of African American (AA) communities on coronavirus disease 2019 (COVID-19) prevalence and death rate within the three most populous counties in each U.S. state and territory ( n =152). Methods: An ecological design was employed for the study. The top three most populous counties of each U.S. state and territory were included in analyses for a final sample size of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…Thirty-nine percent of jobs held by African Americans are in occupations where workers are at risk. From having more sick and vulnerable co-workers as well as more family, friends and neighbors [ 42 , 43 ] African Americans are twice as likely as whites to know someone who has been hospitalized or has died because of COVID- [ 39 ], and they are about 1.4 times more likely to be very concerned about unknowingly spreading COVID to others [ 39 ].…”
Section: African Americans Challenged Resilience: Greater Stress Amentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-nine percent of jobs held by African Americans are in occupations where workers are at risk. From having more sick and vulnerable co-workers as well as more family, friends and neighbors [ 42 , 43 ] African Americans are twice as likely as whites to know someone who has been hospitalized or has died because of COVID- [ 39 ], and they are about 1.4 times more likely to be very concerned about unknowingly spreading COVID to others [ 39 ].…”
Section: African Americans Challenged Resilience: Greater Stress Amentioning
confidence: 99%
“…African Americans’ Threatened Social Cohesion and Mutual Support . Counties with heavier African American representation have considerably more COVID cases and higher COVID death rates [ 37 , 42 , 43 ] pointing to significant social and community impact from COVID. Manifestations include burdened and disrupted social bonds and prosocial community norms from COVID’s spread, reducing family members’ and friends’ capacity for increasingly needed mutual support.…”
Section: African Americans Challenged Resilience: Greater Stress Amentioning
confidence: 99%
“…We also examined whether pro le membership differed by race/ethnicity, particularly given that Black, Indigenous, and people of color (BIPOC) have been disproportionally impacted by the COVID-19 pandemic (Cyrus et al, 2020;Millett et al, 2020). In pregnant women, we observed that Black women were 35% less likely to be members of the passive-coping phenotype, and 70% less likely to be members of the active-coping phenotype.…”
Section: Discussionmentioning
confidence: 96%
“…High incidence and severity of COVID-19 have been reported disproportionately in ethnic/racial minorities. In an ecological study in the three most populous counties in each US state and territory, it was found that for every 1% of African-American density there was a 5% increase in COVID-19 prevalence (p < 0.01) and an increase of 2 deaths due to COVID-19 per 100,000 population (p = 0.02) [ 21 ]. Similarly, Rodriguex-Diaz et al reported that in highly dense Latino communities (≥ 17.8% of the population) in the Northeast and Midwest regions, the rate of COVID-19 cases was higher (adjusted relative risk: 1.42, 95% CI 1.11–1.84 and 1.70, 95% CI 1.57–1.85, respectively) than less densely Latino communities (< 17.8% of the population) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%